Anaylisis Penerapan Program Chse Pada Masa Pandemi Terhadap Kepuasan Pelanggan Di Kenes Bakery & Resto, Jl. Magelang, Sleman, Daerah Istimewa Yogyakarta - Anggraini Retno Wulandari; Hendrajaya; Sapto Supriyanto (Gemawisata: Jurnal Ilmiah Pariwisata, 2023)
The Ministry of Tourism and Creative Economy held a CHSE (Clean, Health, Safety, and Environment Sustainability) program with the aim of restoring tourist confidence and revitalizing tourism during the pandemic. The CHSE program also ensures that the products and services provided meet health protocol standards in the hope of growing interest in visits. Implementation of the CHSE program at Kenes Bakery & Resto Jl. Magelang Km. 5.5 Sleman, DIY has complied with the standard health protocols issued by the Ministry of Tourism and Creative Economy. The CHSE program was implemented at Kenes Bakery & Resto Jl. Magelang Km. 5.5 Sleman, DIY has no effect on customer visiting interest. It was concluded that there were still many customers who did not know about the CHSE program and there were still many customers who had not been able to be disciplined in implementing health protocols and ignored the rules that had been applied.